Origem da população canina de Botucatu/SP como parâmetro de risco de introdução da leishmaniose visceral - Brant, Jonas Lotufo [UNESP]; Costa, Veruska Maia da [UNESP]; Padovani, Carlos Roberto [UNESP]; Langoni, Helio [UNESP]; Modolo, José Rafael [UNESP] (My University, 2010)
The São Paulo state's laws for dogs transport require just a veterinarian health evaluation, with no official control and register by agencies on the entrance of imported animals thus, representing a risk for diseases introduction. The objective of this study was to describe the population of dogs, emphasizing its origin. A questionnaire was applied to 676 dog's owners, representing 4% of vaccinated dogs during the 34th vaccination rabies campaign in 2004. More than 10% of the dogs came from other cities, several of them with visceral leishmaniasis transmission. From those imported animals 74% have lived in Botucatu for more than one year. These findings highlight the importance of identification, register and population control programs of dogs in the state, allowing the establishment of mobility control of these animals, to guarantee information for the decision and definition of strategies to block the spread of diseases.

Las normas de São Paulo, Brasil, para el transporte de perros, sólo requieren el certificado veterinario, y no existe, el control y registro de la entrada de los animales importados, por los organismos oficiales, lo que representa un riesgo de introducción de enfermedades. El estudio describe el origen de la población canina de Botucatu/SP, Brasil, de acuerdo a estudio realizado con 676 propietarios de perros, que representan 4% de los animales vacunados en la 34ª campaña de vacunación antirrábica. Aproximadamente el 10% de los animales procedían de otras ciudades, incluso algunas con transmisión de la leishmaniasis visceral y uno de los animales era originario de otra localidad. De estos animales 74% viven en la ciudad hace más de un año. Estos hallazgos refuerzan la importancia del registro y la identificación de los perros en el estado, permitiendo establecer el control de la movilidad de los animales, asegurando la información para la toma de decisiones y la formulación de estrategias de contención de enfermedades.

As normas do Estado de São Paulo para transporte de cães exigem apenas o atestado de saúde emitido por médico veterinário, inexistindo, controle e registro do trânsito animais, o que representa risco da introdução de doenças como a leishmaniose visceral. Com o objetivo de descrever a origem da população canina de Botucatu/SP, realizou-se inquérito em 676 proprietários de cães durante a 34ª campanha de vacinação anti-rábica do ano de 2004. Cerca de 10% dos animais eram originários de outras cidades, incluindo áreas com transmissão de leishmaniose visceral, sendo um dos animais originário de outro estado. Desses animais, 74% residia na cidade por mais de um ano. Esses achados reforçam a importância do registro e identificação de cães no Estado, permitindo o estabelecimento do controle da mobilidade destes animais, a fim de garantir informações para a tomada de decisão e definição de estratégias de contenção de doenças.
Origin of canine population of Botucatu/SP as a risk parameter of visceral leishmaniasis introduction
Origen de la población canina de Botucatu/SP y el riesgo de introducción de la leishmaniasis visceral
Keywords: Visceral Leishmaniasis; Dogs; Survey; Animal transport; Leishmaniasis visceral; Perros; Investigación; Transporte de animales; Leishmaniose visceral; Cães; Inquérito; Trânsito animal